Assessing L3 Teachers’ Beliefs about Multilingualism: Building, Fine-tuning and Validating a Trilingual Questionnaire - Gutierrez Eugenio, Esther (Working Papers in Language Pedagogy, 2014)
Multilingualism is becoming an everyday reality in today’s society, and so is the learning of third languages (L3s). Despite the paramount role of L3 teachers in the processes of Third Language Acquisition (TLA), little is known so far about L3 teachers’ beliefs about multilingualism. To fill this gap in the literature, a research project was designed to assess the beliefs of teachers of Spanish, French and German as an L3 about a number of issues that have emerged as central in TLA. This paper carefully describes the steps taken in the early stages of this research project: how the overall study was planned, how the research aims and questions were established, how the questionnaire was initially created, how it was piloted and statistically validated with teachers of Spanish as an L3, how these results led to later fine-tuning of the questionnaire, and how the translation of the questionnaire into Spanish, French and German was undertaken. The study concludes by indicating the way in which this second version of the questionnaire will be piloted and validated with teachers of Spanish, French and German as an L3, and the further steps needed to reliably assess the beliefs about multilingualism held by teachers of such languages.